(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article examines the challenges and solutions related to organizing independent learning in higher education institutions of foreign countries. Independent learning is increasingly recognized as a key factor in developing students’ academic autonomy, critical thinking, and lifelong learning skills. The study highlights various international practices that promote effective self-directed education, including the use of foreign study programs, flexible curricula, digital learning platforms, and individualized support systems. It also analyzes the role of institutional structures, faculty mentorship, and cross-cultural exposure in shaping students’ motivation and responsibility in the learning process.